Scalable Fabrication of High Purity Diamond Nanocrystals with Long-Spin-Coherence Nitrogen Vacancy Centers - Trusheim, Matthew E; Li, Luozhou; Laraoui, Abdelghani; Chen, Edward H; Bakhru, Hassaram; Schröder, Tim; Gaathon, Ophir; Meriles, Carlos A; Englund, Dirk (Nano letters, 2014)
The combination of long spin coherence time and nanoscale size has made nitrogen vacancy (NV) centers in nanodiamonds the subject of much interest for quantum information and sensing applications. However, currently available high-pressure high-temperature (HPHT) nanodiamonds have a high concentration of paramagnetic impurities that limit their spin coherence time to the order of microseconds, less than 1% of that observed in bulk diamond. In this work, we use a porous metal mask and a reactive ion etching process to fabricate nanocrystals from high-purity chemical vapor deposition (CVD) diamond. We show that NV centers in these CVD nanodiamonds exhibit record-long spin coherence times in excess of 200 μs, enabling magnetic field sensitivities of 290 nT Hz–1/2 with the spatial resolution characteristic of a 50 nm diameter probe.